Heavy Metals in Mushrooms - Humar, Miha; Širić, Ivan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Numerous scientific research projects are concerned with improving and protecting the environment. The first steps towards solving the problem of environmental pollution include researching and monitoring the presence and concentration of pollutants, especially heavy metals. It is known from previous studies that fungi bioaccumulate high concentrations of heavy metals, the concentration of which depends, to a greater or lesser extent, on factors such as the species, sampling area, and anatomical parts of the fungus, but also the substrate on which they grow. As the concentration of heavy metals in fungi increases, the importance of fungi as bioindicators of environmental pollution also increases. However, extremely high concentrations of toxic heavy metals in fungi can have negative effects on human health. Constantly monitoring and controlling the levels of metals and metalloids in the human diet is necessary, both in foods of plant and animal origin and in food supplements, or in this case edible mushrooms, whose availability on the market and general popularity are constantly increasing. Therefore, this reprint provides good insights into the development of science and technology in relation to heavy metal concentrations in mushrooms.